Погребальный обряд огузов Северного Прикаспия 2-й пол. IX - 1-й пол. XI в. - Круглов, Е.В. (Степи Европы в эпоху средневековья, 2001)
The author describes two groups of sex and age interments, which could be united into one larger rite group on the basis of their common characteristic feature: horse remains, horse scull and extremities, being stacked in the grave filling ups, onto overhead covers, coffin covers, logs, footsteps, and just over human bones, i.e. over the remains of the deceased. Part of the female and infants’ burials contain amulets of ethnographic nature - kopoushky (sort of drop-shaped amulets), bird-shaped tabs and pendants.